2013
DOI: 10.1590/s0100-736x2013000400017
|View full text |Cite
|
Sign up to set email alerts
|

Some virulence genes of Escherichia coli isolated from cloacal swabs of healthy Alagoas Curassows (Pauxi mitu) in Brazil

Abstract: tfraso@usp.br Birds of the Cracidae family (curassows, guans, and chachalacas) are endemic of the Neotropics and 50 species are currently classified. Brazil has 22 species, seven of which are considered threatened. The Alagoas Curassow (Pauxi mitu) species is considered extinct in the wild; but about 120 birds are alive in captivity. Conservation of this species depends entirely on correct management. Health reports of both wildlife and captive curassows are rare. In this study the presence of Escherichia coli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…All the E. coli isolates were able to produce green metallic-sheen colonies on EMB agar, lactose-fermenting pink colonies on MacConkey agar, and amplified E16S gene giving 231 bp amplicon. The present results were in accordance with the findings of earlier studies from Srinagar, India [ 18 ] and Sao Paulo, Brazil [ 8 ], where E. coli was isolated from 80.2% and 78.3% of the poultry fecal samples tested.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…All the E. coli isolates were able to produce green metallic-sheen colonies on EMB agar, lactose-fermenting pink colonies on MacConkey agar, and amplified E16S gene giving 231 bp amplicon. The present results were in accordance with the findings of earlier studies from Srinagar, India [ 18 ] and Sao Paulo, Brazil [ 8 ], where E. coli was isolated from 80.2% and 78.3% of the poultry fecal samples tested.…”
Section: Resultssupporting
confidence: 93%
“…Foodborne disease outbreaks, HUS, TTP, and HC are associated with certain STEC O-serogroups mainly including O157, O26, O91, O103, O121, O113, O111, O145, O45, and O128 as well as untypeable groups [ 3 - 5 ]. Compared to cattle and sheep, which act as major reservoirs of STEC, a limited number of reports have been published on STEC from poultry species and their genetic relatedness with human STEC [ 6 - 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, neither the tsh nor the iutA gene was detected in any tested samples in the current investigation, which attributed to variation in the results obtained by the researchers. In accordance with the previous study, (Saidenberg et al, 2013) illustrated that the frequency of the tsh gene in E. coli avian strains was 85.3%. Another investigation in Egypt by (Abdulgayeid et al, 2015) revealed that the prevalence of the tsh gene in E. coli of diarrheic calves was 100%.…”
Section: Molecular Detection Of E Coli Virulence Genessupporting
confidence: 92%
“…The result of examination of E.coli isolates for the presence of the increased serum survival gene (iss) as shown in photo (3) revealed that (3/11) 27.27% of the examined E.coli strains from raptors bearing the virulence gene (iss).this results is similar to that of Knobl et al (2011) who detected iss gene in 7/24 E. coli isolates in psittassine birds by ratio 29.2%. while higher percentage was detected by Saidenberg et al (2013) who found that the most frequent virulence factor was iss(11/22 isolates)by ratio 50% of E. coli isolates recovered from healthy Alagoas Curassows (Pauximitu) in Brazil The result of investigation of E.coli isolates for the presence of (stx1and stx2) as shown in photo(4) recorded that stx1 was not found in any examined E. coli strain (0/11) 0%, while stx2 was found in (4/11)36.36% of the examined E.coli strains. Similar results are obtained by (Lilian et al, 2017) who revealed that 3/401of E.colisamples are positive for stx2 gene (0.75%) distributed among the orders of Psittaciformes, Strigiformes and Columbiformes.…”
Section: E Detection Of Shiga Toxin 2(stx2) Of E Colimentioning
confidence: 85%